Low-dose-rate induces more severe cognitive impairment than high-dose-rate in rats exposed to chronic low-dose γ-radiation - Ma, Tianbao; Li, Kexian; Sang, Wenjuan; Liu, Xingyu; Luo, Qun; Peng, Ye; Wang, Mingxing; Luo, Xiu; Fang, Jingjing; Wang, Haijun; Wang, Tao; Zuo, Changjing (Frontiers in Public Health, 2024)
Background: Owing to the long penetration depth of gamma (γ)-rays, individuals working in ionizing radiation environments are chronically exposed to low-dose γradiation, resulting in cognitive changes. Dose rate significantly affects radiationinduced biological effects; however, its role in chronic low-dose γ-irradiation-induced cognitive impairment remains unclear. We aimed to investigate whether chronic lowdose γ-irradiation at low-dose-rate (LDR) could induce cognitive impairment and to compare the cognitive alteration caused by chronic low-dose γ-irradiation at LDR and high-dose-rate (HDR).The rats were exposed to γ-irradiation at a LDR of 6 mGy/h and a HDR of 20 mGy/h for 30 days (5 h/day). Functional imaging was performed to assess the brain inflammation and blood-brain barrier destruction of rats. Histological and immunofluorescence analyses were used to reveal the neuron damage and the activation of microglia and astrocytes in the hippocampus. RNA sequencing was conducted to investigate changes in gene expression in hippocampus.The rats in the LDR group exhibited more persistent cognitive impairment than those in the HDR group. Furthermore, irradiated rats showed brain inflammation and a compromised BBB. Histologically, the number of hippocampal neurons were comparable in the LDR group but were markedly decreased in the HDR. Additionally, activated M1-like microglia and A1-like astrocytes were observed in the hippocampus of rats in the LDR group; however, only M1-like microglia were activated in the HDR group. Mechanistically, the PI3K-Akt signaling pathway was upregulated in the HDR group but was downregulated in the LDR group.Compared with chronic low-dose γ-irradiation at HDR, LDR induced more severe cognitive impairment which might involve PI3K/Akt signaling pathway.